DIAGNOSIS AND TREATMENT OF PANCREATOGENIC SEPSIS - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Difficulties in choosing therapeutic and diagnostic tactics for acute pancreatitis are due to the multivector features of the course of this disease. The issues of choosing diagnostic methods and methods of treatment for uncomplicated and complicated, severe and mild pancreatitis, the so-called "edematous" pancreatitis and pancreatic necrosis, complications of pancreatogenic toxemia and destructive complications, sterile and infected pancreatic necrosis, early infection and late destructive complications are discussed.